Collecting ego-centred network data via the Web - Lozar Manfreda, Katja (Metodološki zvezki, 2004)
Owing to their complex data structure face-to-face surveys are a typical data collection method for ego-centred social networks. Usually the interviewer is required to handle the list of alters in order to reduce misunderstandings and typing errors and increase the respondentsć motivation. When answering questions about each alter the respondent is given help. Compared to face-to-face or telephone interviews Web data collection can substantially reduce the costs, time, and fatigue in managing the complex questionnaire required for data collection of ego-centred data. Such data collection is especially suitable for special populations familiar with Internet tools. However, particular attention to questionnaire design has to be paid if a respondent is expected to complete a Web questionnaire by him or herself, compiling a list of alters and giving information about them. One trial in the collection of ego-centred networks via the Web was performed during the annual RIS (Research on Internet in Slovenia) Web survey conducted by the Faculty of Social Sciences, University of Ljubljana. Respondents were randomly split into four groups. Each group received a name generator for one type of social support: material, informational, emotional support or social companionship. Each respondent also received a set of questions for each alter they named in the network generator. Data collection was carried out between June and October 2001. The quality of the data was studied with respect to the number of listed alters and by two question wording forms for name generators. The analysis shows that the Web can be used as a data collection method for ego-centred social networks. However, special attention is required when designing the graphic layout of name generators as well as with the wording of instructions. In particular, the number of alters should be limited in some way, since respondents who name many alters tend to quit the questionnaire before answering additional questions regarding these alters.
Keywords: Data collection; Zbiranje podatkov; Analiza omrežij; Network analysis; družbena omrežja; svetovni splet